Effect of external potassium supply and plant age on the uptake of radiocaesium (137Cs)by broad bean (Vicia faba): interpretation of results from a large-scale hydroponic study - Zhu, Y.G.; Shaw, G.; Nisbet, A.F.; Wilkins, B.T.
Experimental results are presented from a 60 day hydroponic experiment which investigated the simultaneous effects of potassium concentration in solution and plant age on both potassium and radiocaesium (137Cs)uptake by bean plants (Vicia faba)from solutions containing four potassium concentrations. Exponential growth curves were determined for leaf, stem and root tissues of bean plants. Analysis of variance showed that potassium concentration in solution had a significant effect on plant growth, with concentrations of 2 and 4 mg l-1 resulting in greater dry matter accumulation than concentrations of 20 and 40 mg l-1. Net potassium and 137Cs influx rates, normalised to solution concentrations of potassium and 137Cs, were determined for leaf, stem, root and total biomass in growing bean plants. These normalised net influx rates were found to be reduced, in a highly significant way, by both potassium concentration in solution and plant age. These effects were described simultaneously using a multiple linear regression (MLR)equation specific to each plant tissue. Experimentally observed and MLR predicted normalised net influx rates agreed sufficiently well for the MLR equations to be used within a simple rate model of potassium and 137Cs uptake. This rate model, when integrated numerically, reproduced the observed time courses of both potassium and 137Cs concentrations in bean tissues throughout the 60 day hydroponic experiment. The application of the MLR approach to modelling 137Cs uptake by plants is discussed.
Keywords: 137CS; COUNTERMEASURES; MODELLING; PLANT GROWTH; POTASSIUM